Mean variance and goal achieving portfolio for discrete-time market with currently observable source of correlations - Dokuchaev, Nikolai (EDP Sciences, 2010)
The paper studies optimal portfolio selection for discrete time market models in mean-variance and goal achieving setting. The optimal strategies are obtained for models with an observed process that causes serial correlations of price changes. The optimal strategies are found to be myopic for the goal-achieving problem and quasi-myopic for the mean variance portfolio.